2015
DOI: 10.1080/19443994.2014.888678
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and kinetic studies on the adsorption of Ni(II) ion from an aqueous solution using activated carbon prepared from Theobroma cacao (cocoa) shell

Abstract: A B S T R A C TThe adsorption of Ni(II) ion from an aqueous solution was successfully carried out using activated carbon prepared from Theobroma cacao (cocoa) shell, an agricultural solid waste biomass. The activated carbon prepared at ambient temperature (TCAC1) and the one prepared at 350˚C (TCAC2) were characterised by the FT-IR, BET, SEM, EDAX and Particle size analysis methods. The effects of the pH, dosage, initial metal ion concentration and agitation time were studied. The maximum adsorption was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It is suggested as an opportunity to replace the commercial coal-based activated carbon, as it is an eco-friendly product [ 8 ]. There are a few different studies about this subject published by Ahmad et al [ 43 , 44 , 45 ], Kalaivani et al [ 46 ], Ribas et al [ 47 ], Saucier et al [ 48 ], and Plaza-Recobert et al [ 49 ].…”
Section: Cocoa Shell Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested as an opportunity to replace the commercial coal-based activated carbon, as it is an eco-friendly product [ 8 ]. There are a few different studies about this subject published by Ahmad et al [ 43 , 44 , 45 ], Kalaivani et al [ 46 ], Ribas et al [ 47 ], Saucier et al [ 48 ], and Plaza-Recobert et al [ 49 ].…”
Section: Cocoa Shell Applicationmentioning
confidence: 99%
“…Kalaivani et al [ 46 ] reported that activated cocoa shell carbon (TCAC1 and TCAC2) prepared at two different temperatures (30 and 350 °C) show considerable potential for the removal of Ni(II) ion from an aqueous solution. The heat treatment of the adsorbent has resulted in a smaller particle size and larger surface area and, as a result of the increase in adsorption capacity, shows almost 62% higher efficiency in Ni (II) removal, when compared with TCAC1.…”
Section: Cocoa Shell Applicationmentioning
confidence: 99%
“…The silanol group releases H + and forms SiO-which can adsorb Pb(II) (Hu, Wang, & Pan, 2010). The value of n between 1 and 10 represents favorable adsorption (Kalaivani et al, 2014). This study obtained n > 1 for both hydroxyapatite and hydroxyapatite-SiO2 composite.…”
Section: Adsorption Isothermmentioning
confidence: 59%
“…The pH of the solution affects the adsorption capacity of hydroxyapatite-SiO2 to Pb ions. The surface charge of the adsorbent is affected by the pH of the solution (Kalaivani, 2014). The pH of the solution in the adsorption process was studied at range 2-10 using 25 mL of 50 mg/L Pb(II) solution.…”
Section: Effect Of the Ph Solutionmentioning
confidence: 99%
“…This experiment used the pseudofirst order and pseudo-second order models. The former is expressed in the following equation [28]: (2) ...where q t and q 1 are the amounts of phenol adsorbed at t time and at equilibrium condition (mg g -1 ), respectively, while k 1 is the pseudo-first order constant (min -1 ) calculated via slope and intercept of a graph plotted between 1/q t vs 1/t.…”
Section: Adsorption Kineticsmentioning
confidence: 99%